Emotional Intelligence and Academic Performance Among Bachelor Level Nursing Students at a Campus in Kathmandu - Joshi, Sabina; Mukhia, Suzanna; Chand, Ambika (Historical Journal, 2025)
Educational institutions are increasingly recognizing the importance of fostering Emotional Intelligence (EI) alongside academic skills. Many studies have showed that high emotional intelligence correlates with better interpersonal relationships, job satisfaction, leadership qualities, and academic accomplishment. Students face various difficulties in controlling emotions, which impact their learning skills and academic performance. The objective of this study was to find out the level of emotional intelligence and academic performance among bachelor level students. A descriptive cross-sectional design was carried out in nursing campus of Kathmandu. Total enumerative sampling technique was used for data collection. Total sample was 119. Self-administered questionnaire was used for data collection after ethical approval from Institute Review Board of Institute of Medicine was obtained. Data analysis was done with the use of descriptive and inferential statistics. The study findings revealed that 76.5 percent, 18.5 percent and 5.0 percent of the students had average, high and low level of emotional intelligence (EI) respectively. Self-reported academic performance showed that 51.3 percent, 46.2 percent and 2.5 percent of the students were excellent, good and moderate respectively. There was no statistically significant association between emotional intelligence and socio-demographic variables of the respondents (p>0.05). There was a moderate positive correlation (r=0.583) between emotional intelligence and academic performance at the 0.01 level of the significant. The study concluded that most of the students had average level of Emotional Intelligence. Likewise, half of the students had excellent academic performance. Thus, students with high EI tend to have better learning and higher academic achievement. By fostering emotional intelligence, educational institutions can enhance students' overall academic success and prepare them for future challenges.